On the spectrum of critical almost Mathieu operators in the rational case - Jitomirskaya,S; Konstantinov,L; Krasovsky,I (Journal of Spectral Theory, 2022)
We derive a new Chambers-type formula and prove sharper upper bounds on the measure of the spectrum of critical almost Mathieu operators with rational frequencies.